O jornalismo como singular coletivo: reflexões sobre a historicidade de um fenômeno moderno - Phellipy Pereira Jácome (2017)
How to apprehend journalism under the prism of the historicity of its phenomena? In seeking ways to answer this question, this work aims to inquire the normative way in which journalistic activity and its history have been primarily described in its self-referential discourses, especially those related to modernizing ideas. In our view, even in the face of a complex materiality, it is possible to perceive the adoption of a perspective that advocates a strict concept that ties its ism as an empty category of temporal dimensions. This perspective, based on modern values and conceptions, establishes a presentist narrative that tends to consider the past as an inert deposit, without the capacity to affect or to act. This viewpoint is evident, for instance, in the description of Brazilian journalisms modernization in the 1950s, based on the idea of great ruptures and revolutions from a linear and teleological perspective. Thus, the main objective of our work is to explore ways to reopen this past, beholding it as a living tradition and historicizing what we call collective singular. For this, we benefit from the meta-historical categories proposed by Reinhart Koselleck of space of experience and horizon of expectation and we associate them with the considerations of Bruno Latour on the Modern Constitution. This path allows us to critically analyze, from a historical perspective, the gap identified between the promotion of a unique identity - related to journalistic modernization itself - and the variety of ways in which newspapers configure and know the world by their narratives. The work seeks to historicize one and the other, promoting a scrutiny of some texts that compose them, extracted from Brazilian and US newspapers. As a way of making our work methodologically viable, we are attentive to the moments in which this normativity appears even more sedimented in the journalism self-referential speeches, which allows us to draw, from this, a network of broader relations to understand how this ism and its set of modern values are configured, promoted and sustained over time.